DEVELOPMENT OF in vitro METHODS FOR REGENERATION OF STRAWBERRY ‘FESTIVAL’ AND ‘RUBYGEM’ VARIETIES (Fragaria × annanasa Duch.) - Duygu Ayvaz Sönmez; Ebru Kafkas (Acta Scientiarum Polonorum: Hortorum Cultus, 2012)
The cultivated strawberry (Fragaria × ananassa Duch.), a member of the Rosaceae, is the most important soft fruit in the world. In vitro micropropagation is an important tool for clonal multiplication and is commonly applied for induction of somaclonal variation to create genetic variability. Optimized regeneration protocols and high efficiency are also important for gene transformation for improving new cultivars. For this purpose, in this study it was aimed to optimize a regeneration protocol for ‘Festival’ and ‘Rubygem’ strawberry varieties. Leaf disks and stipules from mature in vitro grown strawberry plants of ‘Festival’ and ‘Rubygem’ varieties (Fragaria × annanasa Duch.) were used as explant sources. Mc Cowns Woody plants including vitamins were used as a basal medium. Different concentrations of TDZ (Thidiazuron) (0, 1, 2, 3 and 4 mg l-1) and IBA (Indole-3-butyric acid) (0, 0.2 and 0.4 mg l-1) and the efficiency of 15 days dark treatment on the regeneration from leaf disks and stipules were also tested. Our results suggested that leaf stipules, a high concentration of TDZ, AgNO3 and a dark treatment in culture medium successfully resulted in the induction of regeneration.